Allelopathic potential and allelochemical composition in different soil layers of Rhododendron delavayi forest, southwest China - Quan, Wenxuan; Wang, Anping; Li, Chaochan; Xie, Lijuan (Frontiers in Ecology and Evolution, 2022)
Forests habituated by Rhododendron delavayi often lack understory vegetation, which could possibly be a consequence of allelopathy. It is a phenomenon by virtue of which certain plant species produce allelochemicals that affect the growth and behavior of surrounding plants. To elucidate the allelopathic potential and allelochemicals present in the different layers of a Rhododendron delavayi forest, extracts obtained from three layers of the forest were used for seed germination bioassays and gas chromatography-mass spectrometry (GC–MS) analysis. Aqueous extracts of the litter and humus layers significantly inhibited the seed germination of R. delavayi, Festuca arundinacea, and Lolium perenne, with the litter layer causing the strongest inhibitory effect. A total of 26 allelochemicals were identified in the litter, humus, and soil layers by GC–MS analysis. The primary allelochemicals in the soil and humus layer were organic acids, while the main allelochemicals in the litter layer were phenolic acids. The redundancy analysis revealed the significance of total nitrogen and relative water content in explaining the distribution of the allelochemicals. The results indicated that the litter layer exerted the maximum allelopathic effect due to presence of maximum amount of allelochemical especially the phenolic acids.